2017
DOI: 10.1088/1361-6455/aa9b91
|View full text |Cite
|
Sign up to set email alerts
|

Window for Efimov physics for few-body systems with finite-range interactions

Abstract: We investigate the two lowest-lying weakly bound states of N ≤ 8 bosons as functions of the strength of two-body Gaussian interactions. We observe the limit for validity of Efimov physics. We calculate energies and second radial moments as functions of scattering length. For identical bosons we find that two (N − 1)-body states appear before the N -body ground states become bound. This pattern ceases to exist for N ≥ 7 where the size of the ground state becomes smaller than the range of the two-body potential.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 76 publications
(173 reference statements)
2
11
0
Order By: Relevance
“…The scaled sizes approach constant values in the limit of weak binding for all R . This is in agreement with the study of four-body Brunnian systems 30 and with the recent analysis on the validity limits of Efimov physics 12 . Using the stochastic variational method, both studies concluded that the radius of few-body clusters approaches a constant value for very weak binding.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The scaled sizes approach constant values in the limit of weak binding for all R . This is in agreement with the study of four-body Brunnian systems 30 and with the recent analysis on the validity limits of Efimov physics 12 . Using the stochastic variational method, both studies concluded that the radius of few-body clusters approaches a constant value for very weak binding.…”
Section: Resultssupporting
confidence: 92%
“…The reported size is extrapolated from exact ground-state results and it does not depend on the Lennard-Jones 6–12 potential parameters. In fact, previous variational estimates 12,30 also predicted finite size. This behavior is opposite to the dimer and trimer cases whose scaled size diverges in both cases 3,12,15 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this case, particles are far away and pair potentials barely affect the probability outside the range of the van der Waals potential. That scenario is similar to the one of finite and contact interactions and thus, it is in agreement with previous theoretical findings 10 , 52 that scaled size saturates in the weak binding limit. Weak binding, which does not support smaller clusters, holds pentamers through mediated interactions of additional particles.…”
Section: Resultssupporting
confidence: 92%
“…The Efimov effect was very soon observed in other cold atom systems, including those with non-identical particles and -body systems, in which a variety of universal bound states linked to the Efimov trimer was found. 6 10 . A further unexpected van der Waals universality appeared for three atoms interacting with potential in the ultracold regime, near Feshbach resonances 6 , 7 , 11 13 .…”
Section: Introductionmentioning
confidence: 99%